The Influence of Social Media Digital Marketing Analysis on New Student Acceptance in a University - Salya Rater; Balkhaya (Jurnal Inotera, 2023)
Social media affects the way an individual communicates in terms of sharing and delivering information among fellow users. People spend more time looking for information in this area. Social media digital marketing is a new thing that must be considered when carrying out marketing and advertising strategy activities at universities. The phenomenon of the large number of Indonesian people spending time on social media makes universities. Carry out an advertising strategy on this media. The purpose of carrying out this strategy is to increase the number of visitors to the institution's web, increase brand awareness and recognition as well as manage existing consumers as well as increase sales figures. In this study, the researcher intends to analyze the influence of social media digital marketing on the interest of prospective students by taking a phenomenological qualitative approach.